2019
DOI: 10.1101/791277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly of novel, nuclear dimers of the PI3-Kinase regulatory subunits underpins the pro-proliferative activity of the Cdc42-activated tyrosine kinase, ACK

Abstract: The tyrosine kinase ACK is an oncogene associated with poor prognosis in human cancers. ACK promotes proliferation, in part, by contributing to the activation of Akt, the major PI3-Kinase effector. We show that ACK also regulates PI3-Kinase directly, via interactions with the PI3-Kinase regulatory subunits. ACK interacts with all five regulatory subunit isoforms and directly phosphorylates p85α, p85β, p55α and p50α on Tyr607 (or equivalent). Phosphorylation of p85β at this residue promotes cell proliferation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The site of this phosphorylation was not identified but could, of course, be Tyr607 on p85α, the target site for ACK, which is activated upon insulin stimulation [54]. This would fit with our recent findings of nuclear localised C-terminal dimers of p85 [41].…”
Section: The Nuclear Functions Of Free P85 In Stress Response Pathwayssupporting
confidence: 75%
See 4 more Smart Citations
“…The site of this phosphorylation was not identified but could, of course, be Tyr607 on p85α, the target site for ACK, which is activated upon insulin stimulation [54]. This would fit with our recent findings of nuclear localised C-terminal dimers of p85 [41].…”
Section: The Nuclear Functions Of Free P85 In Stress Response Pathwayssupporting
confidence: 75%
“…C-terminal dimers are instigated by phosphorylation on a conserved tyrosine residue in the iSH2 region; Tyr607 for p85α. p85α is phosphorylated downstream of the insulin receptor at Tyr607 [40] and we have found that it is directly phosphorylated by the non-RTK ACK [41]. ACK binds to all five isoforms of the regulatory subunits and phosphorylates four of them.…”
Section: C-terminal Dimers Of the Pi3k Regulatory Subunitsmentioning
confidence: 99%
See 3 more Smart Citations